Exploring pyrrolidinyl-spirooxindole natural products as promising platforms for the synthesis of novel spirooxindoles as EGFR/CDK2 inhibitors for halting breast cancer cells - Nafie, Mohamed S.; Al-Majid, Abdullah Mohammed; Ali, M.; Alayyaf, Abdulmajeed Abdullah; Haukka, Matti; Ashraf, Sajda; Ul-Haq, Zaheer; El-Faham, Ayman; Barakat, Assem (Frontiers in Chemistry, 2024)
Cancer represents a global challenge, and the pursuit of developing new cancer treatments that are potent, safe, less prone to drug resistance, and associated with fewer side effects poses a significant challenge in cancer research and drug discovery. Drawing inspiration from pyrrolidinyl-spirooxindole natural products, a novel series of spirooxindoles has been synthesized through a one-pot three-component reaction, involving a [3 + 2] cycloaddition reaction. The cytotoxicity against breast cancer cells (MCF-7 and MDA-MB-231) and safety profile against WISH cells of the newly developed library were assessed using the MTT assay. Compounds 5l and 5o exhibited notable cytotoxicity against MCF-7 cells (IC50 = 3.4 and 4.12 μM, respectively) and MDA-MB-231 cells (IC50 = 8.45 and 4.32 μM, respectively) compared to Erlotinib. Conversely, compounds 5a-f displayed promising cytotoxicity against MCF-7 cells with IC50 values range (IC50 = 5.87–18.5 μM) with selective activity against MDA-MB-231 cancer cells. Compound 5g demonstrated the highest cytotoxicity (IC50 = 2.8 μM) among the tested compounds. Additionally, compounds 5g, 5l, and 5n were found to be safe (non-cytotoxic) against WISH cells with higher IC50 values ranging from 39.33 to 47.2 μM. Compounds 5g, 5l, and 5n underwent testing for their inhibitory effects against EGFR and CDK-2. Remarkably, they demonstrated potent EGFR inhibition, with IC50 values of 0.026, 0.067, and 0.04 μM and inhibition percentages of 92.6%, 89.8%, and 91.2%, respectively, when compared to Erlotinib (IC50 = 0.03 μM, 95.4%). Furthermore, these compounds exhibited potent CDK-2 inhibition, with IC50 values of 0.301, 0.345, and 0.557 μM and inhibition percentages of 91.9%, 89.4%, and 88.7%, respectively, in contrast to Roscovitine (IC50 = 0.556 μM, 92.1%). RT-PCR analysis was performed on both untreated and 5g-treated MCF-7 cells to confirm apoptotic cell death. Treatment with 5g increased the gene expression of pro-apoptotic genes P53, Bax, caspases 3, 8, and 9 with notable fold changes while decreasing the expression of the anti-apoptotic gene Bcl-2. Molecular docking and dynamic simulations (100 ns simulation using AMBER22) were conducted to investigate the binding mode of the most potent candidates, namely, 5g, 5l, and 5n, within the active sites of EGFR and CDK-2.